Analysis of Marketing Practices and Identification of Factors Influencing Groundwater Transfer in Tirupur District, India - , Venketesa Palanichamy N; Kalpana M (Archives of Current Research International, 2024)
Water transfers have recently increased as a way to meet water demands in domestic and industrial sectors. Groundwater transfer as the quickest, least expensive, and most environmentally friendly way to address the issue of large cities' water supply and reliability, given the success of the state water system. The water transfers generally focus on the purchase of water from willing sellers in agriculture to meet urban domestic and industrial water demand. Water transfers can generate three different types of impacts namely, direct, indirect and induced impacts. The present study was undertaken mainly to study why groundwater transfer has been an increasing phenomenon over years resulting in pollution hazards and reduction in irrigated area in Tirupur district. The impacts from groundwater transfer to water selling regions and effluent receiving areas are an important consideration in evaluating the impact of groundwater transfer activity. Without doubts groundwater transfer from agriculture to industrial uses would benefit individual sellers, buyers and the Nation as whole. The probability of water selling would increase by 0.1368 per cent, while the water selling intensity by 0.1538 per cent on average for the entire sample. The probability of selling water decreases by 3.62 percent, when farming is the major occupation as well as when profitability from on-farm activities is higher, which in turn made the farmer less reliance on income from water sales. Similarly, the elasticity of intensity of water sales would decrease by 4.07 percent. However, groundwater transfers would cause some economic impediment to local rural communities especially non-sellers. The adverse direct economic impact in groundwater selling or water transferring areas to total revenue in agriculture was Rs. 54.32 lakhs per every crop season. Scarcity of water resulted in shifting of irrigated agriculture to rainfed agriculture and labour intensive to labour less intensive crops.